2015
DOI: 10.1186/s12882-015-0161-y
|View full text |Cite
|
Sign up to set email alerts
|

Traditional medicine practices among community members with chronic kidney disease in northern Tanzania: an ethnomedical survey

Abstract: BackgroundIn sub-Saharan Africa, chronic kidney disease (CKD) is being recognized as a non-communicable disease (NCD) with high morbidity and mortality. In countries like Tanzania, people access many sources, including traditional medicines, to meet their healthcare needs for NCDs, but little is known about traditional medicine practices among people with CKD. Therefore, we sought to characterize these practices among community members with CKD in northern Tanzania.MethodsBetween December 2013 and June 2014, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 38 publications
(20 reference statements)
0
28
0
Order By: Relevance
“…1,2 The prevalence rate in the current study (15.85%) was analogous to prevalence rates varying between 14.6% and 15.8% observed in Asia. 20,21 This finding showed that relatives of CKD patients are at increased risk of CKD possibly because of a genetic link or environmental exposure.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…1,2 The prevalence rate in the current study (15.85%) was analogous to prevalence rates varying between 14.6% and 15.8% observed in Asia. 20,21 This finding showed that relatives of CKD patients are at increased risk of CKD possibly because of a genetic link or environmental exposure.…”
Section: Discussionmentioning
confidence: 92%
“…12 Although reports on the prevalence and risk factors for CKD in family relatives of affected patients exist elsewhere, [13][14][15][16] such invaluable data is scarce in SSA where other potential contributing factors like chronic infections (e.g., HIV/AIDS, 17 hepatitis B and C infections 18 ) and herbal remedies abuse are very frequent and likely to aggravate the burden of CKD. [19][20][21]…”
mentioning
confidence: 99%
“…17 Another peculiarity of CKD in LMICs includes the widespread use of herbal medications that cause chronic interstitial nephritis. 18 Also, the high prevalence of fake and counterfeit medicines (as much as 10%-60%) in LMICs 19,20 may be a significant cause of CKD though not well quantified. The relatively high incidence of hematologic disorders like sickle cell anaemia 21,22 and the sickle cell trait 23,24 and other hemoglobinopathies 24 in West African communities may also contribute to the higher CKD prevalence and increased variability regarding CKD in LMICs.…”
Section: Ckd In Lmicsmentioning
confidence: 99%
“…Individuals living in sub-Saharan Africa may have a heightened CKD risk similar to African Americans due to shared genetic susceptibility, such as that arising from apolipoprotein L1 (APOL1) gene risk variants and sickle cell trait [4][5][6][7]. CKD risk may be further exacerbated by HIV infection and its treatment [8], the rising prevalence of hypertension [9], and diabetes [10], as well as the use of potentially nephrotoxic traditional herbal medicines [11][12][13]. In sub-Saharan Africa, life-saving renal replacement therapy (dialysis or kidney transplantation) is not readily available, and consequently, those who progress to end-stage renal disease (ESRD) die prematurely.…”
Section: Introductionmentioning
confidence: 99%